Conservation and development in Amazonian extractive reserves: the case of Alto Jurua - Ruíz Pérez, M.; Almeida, M.; Dewi, S.; Costa, E.M.L.; Pantoja, M.C.; Puntodewo, A.; Postigo, A.A.; Andrade, A.G. de (2005)
Extractive reserves constitute an innovative approach to match conservation and development objectives, which were originally envisaged as part of a land struggle by forest dwellers in Brazil. In spite of the idea’s popularity and the attempts to apply the concept to different tropical regions, there has been little analysis of the combined conservation and development performance of extractive reserve programs. We present a detailed analysis of deforestation and demographic and socioeconomic changes in Alto Jurua´, the first extractive reserve created in Brazil in 1990. Forest cover has remained fairly stable. Population has declined slightly, with some internal displacements. The cash economy base has shifted from the original rubber production to a diversified portfolio of agriculture and livestock, and there has been a dramatic rise in nonagrarian income. We conclude that the Reserve represents a very dynamic setting with positive conservation and development outcomes during its first decade.